PENERAPAN METODE MENGHAFAL AL-QUR’AN DENGAN MUSHAF BITTIKRAR PADA PROGRAM TAHFIDZ SISWA KELAS X MA AL-HIDAYAH 1 PURWAREJA KLAMPOK BANJARNEGARA - Atta Darojatur Rofi’ah; Siti Lailiyah (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan UNSIQ Jawa Tengah, 2023)
The Qur'an is the word of God which was conveyed to Rasulullah through the angel Gabriel. The first verse of the Quran that was revealed Q.S. Al-Alaq verses 1-5 contain the command to read (iqra '). The reading command is intended so that humans always learn to read and even memorize, the research aims to know the concept of memorizing the Qur'an with the Bittikrar method, to find out how to apply the method of memorizing the Qur'an with the Bittikrar manuscript, and to find out the supporting and inhibiting factors in the application of the Bittikrar method. . This study uses a qualitative approach where the type of research is descriptive with data collection techniques through observation, interviews, and documentation. What will result in the first knowledge of the concept of memorizing the Qur'an with the Bittikrar manuscript method is memorizing without memorizing, the second application of the method with the Bittikrar manuscript efficiently, finally knowing the supporting factors with motivation and balance in learning and memorizing and the inhibiting factor is laziness growing, boredom and environmental influences.